Synthesis of Zinc Oxide and Titanium Dioxide Composite Nanorods and Their Photocatalytic Properties. Issue 1 (January 2016) - Pei, L. Z.; Wei, T.; Lin, N.; Yu, H. Y.
Zinc oxide and titanium dioxide composite nanorods have been synthesized by the hydrothermal process using zinc acetate and titanium butoxide as the raw materials. X-ray diffraction (XRD) shows that the composite nanorods are composed of hexagonal ZnO and tetragonal TiO2 phases. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images show that the length and diameter of the composite nanorods are 1–5 μm and 80–350 nm, respectively. Hydrothermal temperature and duration time have important roles in the formation of the composite nanorods. Using rhodamine B (RB) degradation as the probe reaction, the photocatalytic activities of the composite nanorods under UV light irradiation have been analysed. The roles of the irradiation time, content of the composite nanorods and RB concentration in the photocatalytic activities of the composite nanorods have been investigated. 10 mL 10 mgL −1 RB solution can be totally degraded using 10 mg composite nanorods under UV light irradiation for 90 min.